Using generalized additive models to investigate the environmental effects on pipe failure in clean water networks - Barton, Neal A.; Farewell, Timothy S.; Hallett, Stephen H. (Nature Research (part of Springer Nature), 2020)
Predicting pipe failures using statistical modelling benefits from detailed knowledge of the conditions and circumstances which influence such failures. Incorporating this knowledge into model building improves failure predictions. In this study, we model weather, soil and hydrogeological variables in a generalized additive model for five common pipe materials separately, using partial dependence plots to understand the partial effects of each variable on pipe failure. We show how severe temperatures are associated with high pipe failure. Cold temperatures and air frost and their interaction with soils represent the key factors for pipe failures during the winter for metal pipes. Warm temperatures, high soil moisture deficit and soil movement results in higher pipe failures in asbestos cement pipes during the summer. Warm temperatures, ground movement and soil wash out, and water demand are key factors for polyvinyl chloride pipe failure during the summer. Frost is a key factor influencing polyethylene pipes during winter. An understanding of the physical principals concerning pipe failures can enable the development of more accurate models, guiding network management plans to help reduce asset leakage through appropriate interventions